Performance of CI Engine with Progressive Replacement of Blended Plant Oil by Producer Gas - Singh, R N; Singh, S P; Pathak, B S (Journal of Agricultural Engineering, 2007)
A multi cylinder naturally aspirated diesel engine with matching alternator was operated successfully with mixed fuels (petro-diesel, de-waxed de-gummed Jatropha oil/karanja oil/rice bran oil and Producer gas) and its performance was verified through extensive, short (6 hours) and long duration (30 h) trials. Study revealed that CI engine can also be run on blended de-waxed and de-gummed Jatropha oil with diesel even up to 50%, but preheating of mixture was required at 60degree C to reduce viscosity, when blending of oil with diesel is more than 10%. Maximum blending of plant oil with petro-diesel and its operation with CI engine also depends upon the quality of the plant oil. In case of refined rice bran oil, it was as high as 75%. Maximum replacement of blended plant oil by producer gas was 68% with minor losses in engine output compared to petro-diesel. In general, exhaust gas temperature and specific energy consumption increased in mixed fuel mode with all the three oils, however brake thermal efficiency decreased. It was due to lower calorific value of plant oils and producer gas. In CI Engine having 18.4:1 compression ratio, at 84% engine load and with mixed fuel concentration of pollutants like CO, HC, NO, NO2 was reduced by up to 51, 65, 83 and 85%, respectively. However, in case of rice bran oil, CO concentration increased as compared to petro-diesel.